(untitled) (Applied Biological Research, 2023)
The current therapeutics for Alzheimer’s disorder (AD) is aimed at providing the symptomatic relief from AD and it continues to progress steadily despite ongoing therapy. The present study was aimed to identify the herbal molecules that could utilize multiple pathways of AD pathogenesis for better AD management. One hundred herbal molecules were selected and subjected to docking analysis against acetylcholinesterase (AChE) (1EVE), butyrylcholinesterase (BChE) 4B0P), and Tau protein kinase (1J1B). Based on the docking score, RMSD value, inhibition constant (Ki), and amino acids involved, β-carotene, dihydrotanshinone-I, glabridin, liriodenine, morin, N-formylanonaine, quercetin, quercitrin, rutin, sumaflavone, and vitisinol C were found to be the best molecules. These molecules were then subjected to in vitro screening for their antioxidant and anti-inflammatory potential. Quercetin and rutin were observed to be the most promising antioxidant and anti inflammatory molecules which could be beneficial during AD by targeting the oxidative- and inflammatory-stress pathways. The results predicted that quercetin has potential to target multiple pathways of AD pathogenesis so could prove beneficial in treating AD; however, further analysis is still required.